Brazilian Headache Society: how it all began - Silva-Néto, Raimundo Pereira da (Headache Medicine, 2012)
The Brazilian Headache Society (BHS) was founded on May 19, 1978 thanks to the efforts of Edgard Raffaelli Jr. (1930-2006). He pioneered the study of headache in Latin America and he dedicated his life to this cause. It began with 14 doctors and today, BHS has approximately 400 associate members spread across all regions of the country. Since 1979, the BHS organized an annual scientific meeting (symposium, conference or course).